Assessment of the cluster potential of the Masbate Fish Processing Industry - Albao, Josie Deinla; Posadas, Roger (Quezon City University of the Philippines Diliman, 2012)
This study assesses the cluster potential of the Masbate Fish Processing Industry using Michael Porter's Diamond Model. The objectives of the project are : to provide a detailed description of the industry, to identify its problems, weaknesses and deficiencies and to recommend government interventions that can help transform it into an industrial cluster. Based on the results, the present structure of the industry showed that the established fish processing and semi-processing plants in Masbate is a developed component but its domestic market, most of the supporting organizations and input suppliers are still developing. The fishermen/processors in the industry was shows as a poorly developed component due to their artisanal nature. On the other hand, the relationship that exists between industry components revealed that there is a strong relationship between processing plants and all of its input suppliers, its market link and with some of the support organizations. It further showed that fish suppliers are considered to have strong relationship at present with the fishermen/processors while the rest of the input suppliers are either developing or weak. The study also revealed the problems, weaknesses and deficiencies that are needed to be addressed in order to transform the industry into an industrial cluster. Among the pressing concerns identified are : inability of municipal LGUs to combat illegal fishing which is considered the main threat to the sustainability of the industry, weak relationship between fishermen/processors and support institutions like government and research institutions, lack of entrepreneurial and innovative capability of fishermen/processors, low awareness on food safety and quality among both fishermen/processors and local consumers, lack of access of processors to important market and technology information, and poor diffusion of appropriate technologies to the industry. Present initiatives to boost the industry were likewise revealed in the study. The ongoing implementation of the Integrated Coastal Resource Management Program (ICRMP) in Masbate is significant in creating widespread awareness on fishery resource conservation and protection to all stakeholders. The existence of local government investment incentives and facilities designed to encourage future local and outside investors to the industry is also noteworthy. The presence of all relevant national government agencies in the province like BFAR, DOST, DTI, DOLE and TESDA as well as academic institutions like DEBESMSCAT and MSF signifies that the national government is within reach to respond to critical industry needs like technology, skills, upgrading, innovative product development, marketing information and infrastructure. The Masbate Fish Processing Industry has the potential to be transformed into a cluster provided that basic cluster principles and measures are adopted and implemented to address its problems, weaknesses and deficiencies. Focus must be on facilitating the dynamic interaction of the four major determinants of competitive advantage : a) business strategy, structure and rivalry, b) factor conditions, c) demand conditions, and d) related and supporting industries. Cluster approach, as a new economic development paradigm promotes the idea that interaction, entrepreneurship, learning and productivity can be better achieved by MSMEs if they are close to each other, learning from each other and important players such as government, academic and research institutions are within close proximity to support their economic and innovative activities. This study strongly endorses the idea that local economic development policies should target clusters, rather than individual firms as a feasible option for the socio-economic development of the entire province of Masbate.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Fish trade -- Philippines; Fish processing industry--Masbate.